El concepto de devengo jurídico introducido por el Decreto Legislativo 1425, el principio de asociación, correlación, equiparación o matching, y la aplicación de la NIIF 15 - Casanova-Regis Albi, Roberto José (2020)
Due to the enactment of Legislative Decree Nro. 1425, this paper, points out the relevance of the concept of Juridical Accrual in our tax legal system; as well as the parameters that tax payers must take into account for its correct application in their day-to-day operations, which are understood as economic facts giving rise to taxable events subject to the Corporate Income Tax. On this basis, in order to provide the tools for its correct application of the aforesaid concept, we had incorporated into its analysis, required civil law aspects as they are mentioned by the own juridical definition of Accrual.